Studi Eksegesis Matius 7:21-23 dan Implikasinya Dalam Kehidupan Kekristenan - Heny, Heny (Sekolah Tinggi Teologi Adhi Wacana Surabaya, 2024)
This research was conducted to provide correct insight into using or using these verses according to their context, this is because these verses are often used in the wrong context so that their implications in Christian life will be wrong. This research is qualitative research with an exegetical approach. The results of this research will open insight and correct understanding for those who interpret and preach it, thereby producing correct implications in Christian life.